2021
DOI: 10.1017/s1049023x2100011x
|View full text |Cite
|
Sign up to set email alerts
|

Safe On-Boat Resuscitation by Lifeguards in COVID-19 Era: A Pilot Study Comparing Three Sets of Personal Protective Equipment

Abstract: Introduction: On-boat resuscitation can be applied by lifeguards in an inflatable rescue boat (IRB). Due to Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-COV-2) and recommendations for the use of personal protective equipment (PPE), prehospital care procedures need to be re-evaluated. The objective of this study was to determine how the use of PPE influences the amount of preparation time needed before beginning actual resuscitation and the quality of cardiopulmonary resuscitation (CPR; QCPR) on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 20 publications
(38 reference statements)
0
19
0
Order By: Relevance
“…Recently, the utilization of drones for PPE or automated external defibrillator delivery for communication of safety instructions has been proposed as a potential strategy to encourage, instruct, and reassure rescuers who perform CPR during the pandemic ( 112 ). Finally, the use of a plastic blanket as a quick and alternative PPE has been suggested in order to offer extra protection to the lifeguards during on-boat resuscitation without any delay of the CPR initiation ( 113 ).…”
Section: Other Protective Measures Proposed For Cpr Providersmentioning
confidence: 99%
“…Recently, the utilization of drones for PPE or automated external defibrillator delivery for communication of safety instructions has been proposed as a potential strategy to encourage, instruct, and reassure rescuers who perform CPR during the pandemic ( 112 ). Finally, the use of a plastic blanket as a quick and alternative PPE has been suggested in order to offer extra protection to the lifeguards during on-boat resuscitation without any delay of the CPR initiation ( 113 ).…”
Section: Other Protective Measures Proposed For Cpr Providersmentioning
confidence: 99%
“…The effect of PPE on resuscitation is not yet consistent. While some studies have found no significant change in the CPR quality [ 17 , 18 ], a recent systematic review suggests that PPE may affect the rate and depth of cardiac compressions (CC) [ 2 ]. Despite that, the resuscitation time in all studies reviewed did not exceed 4 min.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the current COVID-19 pandemic, increasing attention has been focussed on the personal protective equipment (PPE) worn by rescuers. As a consequence, aquatic rescue organizations around the world are re-evaluating their resuscitation protocols, seeking on the one hand to avoid contamination of rescuers as much as possible, while on the other hand assuring high quality resuscitation ( 25 27 ). The results of the current study may be of interest to rescue organizations, as they do not demonstrate a profound negative effect of the heavy survival suits with life jackets on BLS quality.…”
Section: Discussionmentioning
confidence: 99%